Self-objectification and career aspirations among young Chinese women: the roles of self-esteem and career decision-making self-efficacy - Sun, Qingqing (Frontiers in Psychology, 2023)
This study explored the relationship between self-objectification and career aspirations among young women from the perspective of objectification theory. A sample of 439 Chinese undergraduate women completed questionnaires on self-objectification, self-esteem, career decision-making self-efficacy, and career aspirations. The results revealed that self-objectification was negatively correlated with self-esteem, career decision-making self-efficacy, and career aspirations.Self-esteem and career decision-making self-efficacy, both independently and serially, mediated the association between self-objectification and career aspirations. These results provide a better understanding of the negative consequences of self-objectification for career aspirations.